2016
DOI: 10.1002/anie.201608653
|View full text |Cite
|
Sign up to set email alerts
|

Microsecond Timescale Dynamics of GDP‐Bound Ras Underlies the Formation of Novel Inhibitor‐Binding Pockets

Abstract: The recent discovery of inhibitory compounds binding to distinct pockets on GDP-bound Ras has renewed the view on the druggability of this crucial cancer driver. However, the origin of these pockets, which are not readily formed in the crystal structure in the absence of the compounds, is yet unclear. Herein, we explored the intrinsic flexibility of Ras⋅GDP on microsecond to millisecond timescales using relaxation-based NMR experiments, and identified substantial slow dynamics with τ of 34 μs at 5 °C, which ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 39 publications
4
28
1
Order By: Relevance
“…This is particularly true for pockets p1, p2, and p4 that are proximal to SW1 and SW2 (Figure a), while the distal pocket p3 is allosterically coupled with these regions (Gorfe et al., ; Grant et al., ). This observation is consistent with a recent relaxation‐based NMR study, which found that opening of binding pockets on RAS is a result of intrinsic conformational dynamics (Mao, Yao, Wang, Cheng, & Long, ). Similarly, the polar and non‐polar solvent accessible surface areas of preselected residues that define p1 undergo significant fluctuations, with the latter also exhibiting large variability among the mutants.…”
Section: Resultssupporting
confidence: 92%
“…This is particularly true for pockets p1, p2, and p4 that are proximal to SW1 and SW2 (Figure a), while the distal pocket p3 is allosterically coupled with these regions (Gorfe et al., ; Grant et al., ). This observation is consistent with a recent relaxation‐based NMR study, which found that opening of binding pockets on RAS is a result of intrinsic conformational dynamics (Mao, Yao, Wang, Cheng, & Long, ). Similarly, the polar and non‐polar solvent accessible surface areas of preselected residues that define p1 undergo significant fluctuations, with the latter also exhibiting large variability among the mutants.…”
Section: Resultssupporting
confidence: 92%
“…In principle, the residual Ras⋅GDP signals can be specifically subtracted out from the RD/CEST data sets ( S exp ) by postprocessing that exploits information from the same experiments recorded with a pure Ras⋅GDP sample using identical settings. The earlier finding that the internal dynamics of Ras⋅GDP are on the μs timescale, outside the active time windows of 15 N RD and CEST experiments, further simplifies the approach. A 2D reference plane ( S ref ) recorded with a single CPMG field strength/B 1 offset, instead of a full RD/CEST dataset on Ras⋅GDP, would be sufficient for this postprocessing, (see the Supporting Information for details).…”
Section: Figurementioning
confidence: 63%
“…However, increasing evidence shows that both the active and inactive forms of Ras are inherently flexible, populating transiently formed alternative conformations. In a recent study, substantial internal dynamics of Ras⋅GDP with an exchange lifetime of 34 μs were captured by relaxation‐based NMR experiments, revealing a sparsely populated conformational state with important “druggable” pockets . On a much slower timescale, Ras⋅GTP was also found to interconvert between a major and a minor conformer (termed states 2 and 1, respectively), with state 2 generally regarded as the effector‐competent state .…”
Section: Figurementioning
confidence: 99%
“…The effector and nucleotide-binding sites of the effector lobe partially overlap, located on opposing sides of the segment named switch I (residues [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Further regions participating in hosting the nucleotide are the phosphate-binding Ploop (residues 10-17) and switch II (residues 57-76) of the effector lobe [7,9] and the nucleobase binding-loops of the allosteric lobe (residues 116-120 and 145-147) [7].…”
Section: Ras Proteins: Structure Dynamics and Functionmentioning
confidence: 99%
“…Slow dynamics of GDP-bound H-Ras(1-171) was also investigated together with its Gly12Val oncogene mutant by relaxation dispersion measurements of bilinear coherences as well as classical CPMG experiments performed at 5°C [30]. The authors found that the α1, α2, α3, L2, L4 loops, central β1-β3-sheet lining the binding pockets of previously described inhibitors for Ras, undergo large changes on slow time scale, suggesting the possibility of selective targeting of some of them.…”
Section: Dynamics In Small-molecule Bindingmentioning
confidence: 99%